التقديم والتأخير في عمدة الجملة الاسمية وأغراضهما: كتاب عظة الناشئين لمصطفى الغلاييني أنموذجا (دراسة تحليلية نحوية): Preposing and Postposing in the Core Elements of Nominal Sentences and Their Purposes: A Syntactic Analysis of Muṣṭafā Al-Ghalāyīnī’s ʿiẓat Al-Nāshīʾīn - Fanisa Aulia Putri; Muhammad Syamsul Arifin (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
Muṣṭafā al-Ghalāyīnī’s ʿIẓat al-Nāshīʾīn is a renowned work known for instilling values of morality, etiquette, and nationalism since colonial times. The phenomena of taqdīm (preposing) and taʾkhīr (postposing) in this text play a crucial role in shaping the reader’s understanding of the content, making it essential to clarify their meanings to avoid misinterpretation of the intended message. This study aims to identify the types of taqdīm and taʾkhīr in the core components of nominal sentences (jumla ismiyyah) and explain their purposes as found in ʿIẓat al-Nāshīʾīn. The study adopts a qualitative methodology, applying three approaches: descriptive for data analysis, library research for data collection and object study, and theoretical linguistics as the analytical framework. Data were collected from 1,120 sentences across 44 sections, with 15 selected purposively as samples. The data collection technique used is simak (observation), including listening, transcribing, and recording, followed by analysis using the distributional method with direct constituent analysis and syntactic segmentation. The findings reveal variations of taqdīm and taʾkhīr in nominal sentence structures, totaling 533 sentences. These include obligatory and permissible preposing/postposing of the subject (mubtadaʾ) and predicate (khabar), including in kāna and inna constructions. The purposes of taqdīm and taʾkhīr include emphasis, specification, drawing special attention, comparison, reasoning, expression of hope, reinforcement of meaning, informing unaware interlocutors, semantic restriction (qaṣr), and affirming intent or eliminating doubt. The study recommends that future researchers analyze taqdīm and taʾkhīr in verbal sentences (jumla fiʿliyah), understand the order of core versus supplementary elements (ʿumda vs. faḍla), or adopt a historical-comparative linguistic (diachronic) approach.